Determinants of Smartphone Purchase Decisions: The Role of Product Quality, Price Perception, Brand Image, and Lifestyle Among Management Students - Narto, Eko; Hasan, Muh; Daud, Agung (Digital Business Journal, 2025)
In the digital era, smartphones have become essential consumer products, particularly among young consumers such as university students. Apple’s iPhone, as a premium smartphone brand, continues to attract attention due to its strong brand image and innovative features. However, understanding the factors that influence purchasing decisions among specific consumer segments remains crucial for both marketers and academics. This study aims to examine the influence of product quality, price perception, brand image, and lifestyle on iPhone purchasing decisions among students of the Management Study Program at Muhammadiyah University, Class of 2020. The research employed a quantitative approach, using a structured questionnaire distributed to a sample of 86 respondents selected through the Slovin technique. Data were analyzed using multiple linear regression with the support of SPSS version 25. The findings indicate that product quality, price perception, brand image, and lifestyle all have a positive and significant impact on purchasing decisions. Furthermore, these variables collectively contribute significantly to explaining consumer behavior in the context of premium smartphone purchases. This study contributes to the existing literature by integrating multiple consumer behavior theories within a single framework applied to a young and dynamic consumer group in an emerging market context. The results offer practical insights for marketers aiming to enhance brand positioning and marketing strategies targeting university students. Additionally, the study provides a foundation for future research on consumer decision-making in technology product markets.